2014
DOI: 10.1016/j.jana.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Nonoccupational Postexposure HIV Prophylaxis in Sexual Assault Programs: A Survey of SANE and FNE Program Coordinators

Abstract: This cross-sectional study describes Sexual Assault Nurse Examiner (SANE)/Forensic Nurse Examiner (FNE) program practices related to HIV testing, non-occupational post-exposure prophylaxis (nPEP), and common barriers to offering HIV testing and nPEP. A convenience sample of 174 SANE/FNE programs in the United States and Canada was drawn from the International Association of Forensic Nurses database, and program coordinators completed web-based surveys. Three quarters of programs had nPEP policies, 31% provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…Collectively, the evidentiary literature recommendations for practice include: 1) developing a clinical decision tool that rapidly, efficiently, and accurately assesses the risk of HIV transmission following sexual assault, 2) developing evidence-based, standardized HIV (N) PEP protocols tailored to meet community needs, and 3) consultation with multi-disciplinary experts to provide education and training on use of (N)PEP guidelines/protocols/tool. Additional studies indicated that since the publication of updated guidelines in 2010 HIV (N) PEP has been offered more frequently [16,17]; however, the rates remain remarkably low. Studies that provided site-specific guidelines and /or protocols were most successful at offering HIV (N) PEP appropriately [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, the evidentiary literature recommendations for practice include: 1) developing a clinical decision tool that rapidly, efficiently, and accurately assesses the risk of HIV transmission following sexual assault, 2) developing evidence-based, standardized HIV (N) PEP protocols tailored to meet community needs, and 3) consultation with multi-disciplinary experts to provide education and training on use of (N)PEP guidelines/protocols/tool. Additional studies indicated that since the publication of updated guidelines in 2010 HIV (N) PEP has been offered more frequently [16,17]; however, the rates remain remarkably low. Studies that provided site-specific guidelines and /or protocols were most successful at offering HIV (N) PEP appropriately [16].…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies indicated that since the publication of updated guidelines in 2010 HIV (N) PEP has been offered more frequently [16,17]; however, the rates remain remarkably low. Studies that provided site-specific guidelines and /or protocols were most successful at offering HIV (N) PEP appropriately [16].…”
Section: Discussionmentioning
confidence: 99%
“…Perpetrators of sexual assault are considered to be a high-risk population for HIV infection and PEP should be offered for these cases. 3941 …”
Section: Assessment Of the Need For Occupational And Non Occupationalmentioning
confidence: 99%
“…Typically, prophylaxis is offered at the close of the exam. When patients accept the offer of nPEP, they are given the first dose immediately and often discharged with a three to five day starter pack of medications; however, the amount of medication, cost of the medication regimen, and who pays that cost varies from jurisdiction to jurisdiction, and forensic nursing program to program (Draughon, Anderson, Hansen, & Sheridan, 2014). …”
mentioning
confidence: 99%